Global Volunteering in Orthopaedics: Availability and Implementation Considerations. Issue 4 (15th February 2021) - Babu, Jacob M.; Cruz, Aristides; Patel, Shyam A.; Born, Christopher T.; Akelman, Edward
Abstract : The World Health Organization describes traumatic injuries as a "neglected epidemic" in developing countries, accounting for more deaths annually than HIV/AIDS, malaria, and tuberculosis combined. Low- and middle-income countries rely on volunteer assistance to address the growing surgical disease burden of traumatic injuries. Efforts to increase the availability of international electives for orthopaedic trainees can help with the short-term need for surgical personnel abroad and facilitate sustainability through capacity building, maximizing long-term benefits for all parties. The volunteer invariably benefits from this cross-cultural experience with many citing improved skills in communication, clinical diagnostics, appreciation of equality and diversity, and cost-consciousness. A consolidated discussion regarding barriers and implementation strategies can assist interested individuals and institutions plan for future volunteering endeavors.